Limited Şirkette Bağlılık Yükümü ve Rekabet Yasağı - Bağrıaçık, Safiye Nur (Seçkin Yayıncılık, 2017)
6102 sayılı Türk Ticaret Kanunu’nda (TTK) şirket ortaklarına ve yönetici-lerine yeni bir takım haklar getirilmiştir. “Limited Şirkette Bağlılık Yükümü ve RekabetYasağı” 6762 sayılı TTK’da müdürler için bulunan ancak limited şirket ortakları için de6102 sayılı TTK ile getirilen bir yükümlülük olmuştur. Bu kapsamda öncelikle TTKm.613 “Bağlılık Yükümü ve Rekabet Yasağı” hükmü başta olmak üzere TTK m. 626 veTTK m.437/3 hükümleri incelenmiştir. Bağlılık yükümü ve rekabet yasağına tabi olankimseler hakkında bilgi verilmiştir. Bağlılık yükümü ve rekabet yasağına aykırılık so-nucunda uygulanacak yaptırımlar açıklanmıştır. Çalışma da yer yer anonim şirket hü-kümlerine de yer verilmiştir.

A new set of rights has been introduced to company partners and managers in the Turkish Commercial Code (TCC) No: 6102. “Loyalty Duty and Non- Compete Obligation in Limited Liability Company” was an obligation brought by TCC No. 6762 for directors but limited liability company shareholders by TCC No. 6102. In this context, firstly, the provision of the Turkish Commercial Code, m. 613, "Liability of Loyalty and Non-Compete Obligation" TCC article 626 and TCC article 437 /3 have been examined. Information has been given to persons who are subject to loyalty obligations and non-compete obligation. The sanctions to be imposed as a result of contradiction to this law are also explained. The study was also included in the provisions of joint stock companies.
Loyalty Duty and Non-Compete Obligation in Limited Liability Company
Keywords: Türk Ticaret Kanunu; Limited Şirket; Bağlılık Yükümü; Rekabet Yasağı; Sır Saklama Yükümlülüğü; Turkish Commercial Code; Limited Liability Company; Loyalty Duty; Non-Compete Obligation; Confidentiality Obligation